Silicon to improve the quality of melon (Cucumis melo l.) and cucumber (Cucumis sativus l.) seedlings (Bioagro, 2026)
The addition of silicon (Si) represents a promising avenue to address agricultural challenges, providing enhancing effects on plant defense mechanisms, growth, photosynthesis, and fruit production. Therefore, the objective of this research was to understand the response of melon and cucumber to different doses of silicon on plant growth and seedling quality.  Seeds of the Harper melon variety Palmira F1 and the slicer cucumber variety Modan RZ F1 (22-951) were sown in 60-cell seedling trays filled with peat moss (Berger®), maintained inside a growth chamber with artificial lighting, with a light environment of 305,3 μmol m-2·s-1 of DFFF (photosynthetic photon flux density). A completely randomized experimental design was used, with five treatments: Si at doses of 0 (control), 1, 3, 5, and 7 mg·L-1 (Sodium metasilicate®, Na2SiO3.9H2O). Treatments were applied to tray-grown plants through irrigation. Response variables included plant height (PH), leaf area (LA), stem diameter (SD), leaf greenness (LGB), dry root biomass (DRB), dry aerial biomass (AAB), total biomass (TB) of seedlings, slenderness index (SI), shoot-to-root ratio (SRR/RPR), and Dickson quality index (DQI). Silicon in melon and cucumber seedlings improved growth and quality-related parameters (SRR, SBB, TB, and DQI), with a higher DQI level in seedlings treated with a dose of 1 mg L-1.
Keywords: Greenness; growth; root biomass; seedling quality